Excellent adsorption capacity and photocatalytic regeneration of nanoparticles-assembled mesoporous Cu2O/Bi2O3 composites for removal of methyl orange. (31st May 2019) - Tang, Hongying; Yang, Wulin; Fu, Licai; Zhu, Jiajun; Li, Deyi; Zhou, Lingping
Abstract: A series of novel nanoparticles-assembled Cu2 O/Bi2 O3 composites were synthesized by simple wet chemical reduction method. The synthesized materials were characterized by XRD, SEM, BET and FTIR. The microstructures are considered to be the nanoparticles-assembled mesoporous structure with large specific surface. The composited Bi2 O3 refine the grain of Cu2 O and increase the surface area of composites. When the molar ratio of composite is 5:1, the sample shows excellent adsorption capacity of removing methyl orange and the maximum adsorption capacity is 1533.2 mg g −1 . The performance of adsorption is attributed to the synergistic effects of high specific surface area and electrostatic interaction. In this work, the adsorption kinetic was investigated, which follows the pseudo-second-order kinetic model for the adsorption of methyl orange. The Cu2 O/Bi2 O3 composites can be reused through further photocatalytic regeneration. The results indicate that the adsorption-photocatalysis have great potential in water treatment applications.